Orthogonal DF Cooperative Relay Networks with Multiple-SNR Thresholds and Multiple Hard-Decision Detections - Dian-Wu Yue (EURASIP Journal on Wireless Communications and Networking, 2010)
This paper investigates a wireless cooperative relay network with multiple relays communicating with the destination over orthogonal channels. Proposed is a cooperative transmission scheme that employs two signal-to-noise ratio (SNR) thresholds and multiple hard-decision detections (HDD) at the destination. One SNR threshold is used to select transmitting relays, and the other threshold is used at the destination for detection. Then the destination simply combines all the hard-decision results and makes the final binary decision based on majority voting. Focusing on the decode-and-forward (DF) relaying protocol, the average bit error probability is derived and diversity analysis is carried out. It is shown that the full diversity order can be achieved by setting appropriate thresholds even when the destination does not know the exact or average SNRs of the source-relay links. The performance analysis is further extended to multi-hop cooperation and/or with the presence of a direct link where multiple thresholds are needed. By combining the multiple-SNR threshold method with a selection of the best relaying link, a high spectral-efficiency cooperative transmission scheme is further presented. Simulation results verify the theoretical analysis and demonstrate performance advantage of our proposed schemes over the existing ones.